DgCspC gene overexpression improves cotton yield and tolerance to drought and salt stress comparison with wild-type plants - Xia, Wenwen; Zong, Jiahang; Zheng, Kai; Wang, Yuan; Zhang, Dongling; Guo, Sandui; Sun, Guoqing (Frontiers in Plant Science, 2022)
Drought and high salinity are key limiting factors for cotton quality and yield. Therefore, research is increasingly focused on mining effective genes to improve the stress resistance of cotton. Few studies have demonstrated that bacterial Cold shock proteins (Csps) overexpression can enhance plants stress tolerance. Here, we first identified and cloned a gene DgCspC encoding 88 amino acids (aa) with an open reading frame (ORF) of 264 base pairs (bp) from a Deinococcus gobiensis I-0 with high resistance to strong radiation, drought, and high temperature. In this study, heterologous expression of DgCspC promoted cotton growth, as exhibited by larger leaf size and higher plant height than the wild-type plants. Moreover, transgenic cotton lines showed higher tolerance to drought and salts stresses than wild type plants, as revealed by susceptibility phenotype and physiological indexes. Furthermore, the enhanced stresses tolerance was attributed to high capacity of cellular osmotic regulation and ROS scavenging resulted from DgCspC expression modulating relative genes up-regulated to cause proline and betaine accumulation. Meanwhile, photosynthetic efficiency and yield were significantly higher in the transgenic cotton than in the wild-type control under field conditions. This study provides a newly effective gene resource to cultivate new cotton varieties with high stresses resistance and yield.